Posttransplant Lymphoproliferative Disorder Presenting as Testicular Lymphoma in a Kidney Transplant Recipient: A Case Report and Review of the Literature. (14th February 2018) - Obanor, Steve Omoruyi; Gruttadauria, Michelle; Applebaum, Kayla; Eskandari, Mohammad; Lieberman Lubetzky, Michelle; Greenstein, Stuart
Abstract : Posttransplant lymphoproliferative disorder (PTLD) is a malignancy caused by the immunosuppression that occurs after transplantation. It is primarily a nodal lesion but frequently it involves extranodal masses. Treatment is usually by reducing immunosuppressive therapy. Testicular lymphoma as PTLD is notably rare in documented literature and there is limited evidence of definitive treatment guidelines. This manuscript describes a patient who developed diffuse large B-cell lymphoma of his right testis one year following kidney transplantation. A diagnosis of PTLD was made and treatment with rituximab, locoregional radiotherapy, and intrathecal methotrexate in addition to the standard reduction of immunosuppression resulted in complete remission until now. We submit this case along with literature review of similar cases in the past and a review of specific peculiarities of our case with emphasis on our treatment plan to further the understanding of this diversiform disease.